New antimicrobial cyclolignan and others constituents from the leaves of Scyphocephalium mannii (Benth. & Hook.f.) Warb. Issue 23 (1st December 2022) - Nganteng, Dieu Ne Dort; Melong, Raduis; Maffo, Timoleon; Tchuenguem, Roland T.; Crochet, Aurelien; Dzoyem, Jean Paul; Wafo, Pascal; Bochet, Christian G.; Ngadjui, Bonaventure Tchaleu
Abstract: Chemical investigation of the MeOH extract of the leaves of Scyphocephalium mannii (Benth. & Hook.f.) Warb. (Myristicaceae) led to the isolation and characterization of one new metabolite ( + )-(7' S, 8 S, 8' S )-4, 4'-dihydroxy-3, 3', 5, 5'-tetramethoxy-2, 7'-cyclolignan (1 ) along with five known compounds. Their structures were elucidated by spectroscopic means, including 1 D and 2 D NMR, HRESI-MS and by comparison with published data. The absolute configuration of compound 1 was determined by single-crystal X-RAY diffraction. Compound 1 showed moderate antifungal activity against Cryptococcus neoformans with respective MIC and MMC values of 64 and 256 µg/mL. Graphical Abstract: UF0001